ANALYSIS OF RETURN ON LOAN PRINCIPAL AND UJRAH/ MU'NAH FOR RAHN AND ARRUM EMAS PRODUCTS AT SHARIA PAWNSHOPS IN LHOKSEUMAWE CITY - Nurul Mawaddah; Anwar Puteh; Haris Al-Amin (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
This study aims to determine the analysis of loan principal repayments and Ujrah / Mu'nah products of Rahn and Arrum Emas at Sharia Pawnshops in Lhokseumawe City. The type of research used is descriptive qualitative research. This research has been surveyed from 2020, where one of the loan agreements as a case study will end in 2022. The type of data used is qualitative data. The data sources used are primary data and data collection methods through direct interviews with employees, branch managers, randomly selected customers and general company data that can be accessed directly via the pawnshop link. The analytical method used is descriptive qualitative analysis. The research results show that every customer deciding on one of these contracts has certain considerations both in terms of the ability to pay all at once or in installments. Everything is tailored to the needs and income generated. The amount of ujrah or mu'nah determination, especially for Arrum Mas products, uses a flat calculation, where the loan principal and mu'nah are the same for each installment payment, which is 1 percent per month of the loan amount. The ujrah or mu'nah from Arrum Mas products is lower than Rahn products if the payment is calculated at maturity. The amount of ujrah or mu'nah determination, especially for Arrum Mas products, uses a flat calculation, where the loan principal and mu'nah are the same for each installment payment, which is 1 percent per month of the loan amount. The ujrah or mu'nah from Arrum Mas products is lower than Rahn products if the payment is calculated at maturity. The amount of ujrah or mu'nah determination, especially for Arrum Mas products, uses a flat calculation, where the loan principal and mu'nah are the same for each installment payment, which is 1 percent per month of the loan amount. The ujrah or mu'nah from Arrum Mas products is lower than Rahn products if the payment is calculated at maturity.